Challenges of Using Google Translate as a Tool to Enhance Essay Writing Skill - Agustin, Arista; Raissa Salsabila, Fairuz; Agustin, Rita; Persita Dewi, Bella (English Education, Linguistics, and Literature Journal, 2025)
The use of Google Translate has become increasingly common in student environments as a tool to advance essay writing skills. This research aims to explore the role of Google Translate in advancing students' experience and skills in essay writing and to identify the barriers and limitations associated with its use. The research used a descriptive qualitative method with a focus on a questionnaire that collected open-ended responses from participants. The research concerned 25 students enrolled in the English department at Tidar University who had used Google Translate in their writing. The results were collected through a questionnaire designed to elicit detailed feedback on students' perceptions, frequency of use, motivations, challenges, and suggestions for alternative tools. The findings show that most students often rely on Google Translate to help with writing. They argued that while this tool helps in providing quick translations and vocabulary, it also has limitations, such as grammatical inaccuracies and overly addictive styles, which can be a hindrance to the development of fundamental writing skills. In addition, the students pointed out the importance of manual writing skills for deeper language understanding and creativity.